Mouse embryonic stem cell-derived cardiomyocytes cease to beat following exposure to monochromatic light: association with increased ROS and loss of calcium transients - Singh, Gurbind (Am J Physiol Cell Physiol, 2019)
We earlier established the mouse embryonic stem (ES) cell “GS-2” line expressing enhanced green fluorescent protein (EGFP) and have been routinely using it to understand the molecular regulation of differentiation into cardiomyocytes. During such studies, we made a serendipitous discovery that functional cardiomyocytes derived from ES cells stopped beating when exposed to blue light. We observed a gradual cessation of contractility within a few minutes, regardless of wavelength (nm) ranges tested: blue (~420–495), green (~510–575), and red (~600–700), with green light manifesting the strongest impact. Following shifting of cultures back into the incubator (darkness), cardiac clusters regained beatings within a few hours. The observed light-induced contractility-inhibition effect was intrinsic to cardiomyocytes and not due to interference from other cell types. Also, this was not influenced by any physicochemical parameters or intracellular EGFP expression. Interestingly, the light-induced cardiomyocyte contractility inhibition was accompanied by increased intracellular reactive oxygen species (ROS), which could be abolished in the presence of N-acetylcysteine (ROS quencher). Besides, the increased intracardiomyocyte ROS levels were incidental to the inhibition of calcium transients and suppression of mitochondrial activity, both being essential for sarcomere function. To the best of our knowledge, ours is the first report to demonstrate the monochromatic light-mediated inhibition of contractions of cardiomyocytes with no apparent loss of cell viability and contractility. Our findings have implications in cardiac cell biology context in terms of 1) mechanistic insights into light impact on cardiomyocyte contraction, 2) potential use in laser beam-guided (cardiac) microsurgery, photo-optics-dependent medical diagnostics, 3) transient cessation of hearts during coronary artery bypass grafting, and 4) functional preservation of hearts for transplantation.